Variability in Genomic and Virulent Properties of Porphyromonas gingivalis Strains Isolated From Healthy and Severe Chronic Periodontitis Individuals - Mendez, Katterinne N.; Hoare, Anilei; Soto, Cristopher; Bugueño, Isaac; Olivera, Marcela; Meneses, Claudio; Pérez-Donoso, Jose Manuel; Castro-Nallar, Eduardo; Bravo, Denisse (Frontiers in Cellular and Infection Microbiology, 2019)
P. gingivalis has been extensively associated with both the onset and progression of periodontitis. We previously isolated and characterized two P. gingivalis strains, one from a patient exhibiting severe chronic periodontitis (CP3) and another from a periodontally healthy individual (H3). CP3 strain possessed higher ability of forming biofilms and invade gingival epithelial cells, compared to H3. Here, we aimed to determine whether differences in virulence between these two strains could be explained by the presence or absence of specific genes encoding virulence factors. We sequenced the whole genome of both P. gingivalis CP3 and H3 and conducted a comparative analysis regarding P. gingivalis virulence genetic determinants. To do so, we performed a homology search of predicted protein sequences in CP3 and H3 genomes against the most characterized virulent factor genes for P. gingivalis available in the literature. In addition, we performed a genomic comparison of CP3 and H3 with all the 62 genomes of P. gingivalis found in NCBI Genome database. This approach allowed us to determine the evolutionary relationships of CP3 and H3 with other virulent and avirulent strains; and additionally, to detect variability in presence/absence of virulent factors genes among P. gingivalis genomes. Our results show differences the hemagglutinin genes. While CP3 possesses one copy of hagA and two of hagC, H3 has no hagA and only one copy of hagC. Experimentally, this finding is related to lower in vitro hemmaglutination ability of H3 compared to CP3. Moreover, while CP3 encodes a gene for a major fimbrium subunit FimA type 4 (CP3_00160), H3 possess a FimA type 1 (H3_01400). Such genetic differences are in agreement with both lower biofilm formation ability and less intracellular invasion to oral epithelial cells exhibited by H3, compared with the virulent strain CP3. Therefore, in this work, we first performed an in silico analysis of two strains isolated from subjects showing distinct periodontally health status. We next evaluated if the differences found in their genomes had an effect in critical virulence steps in vitro. Through such analysis, we are contributing to the understanding of P. gingivalis role in both health and disease.